Control formation of rigid linear and flexible zig-zig complexes based on Zn(II) and hydroxyquinoline carboxylate ligand system - Mal, Dasarath
Two novel zinc complexes, [Zn(H-hqc)(2)(bpy)(H2O)(2)] (1) and [Zn(H-hqc)(2)(bpe)]center dot H2O (2), where H-2-hqc=2-hydroxyquinoline-4-carboxylic acid, bpy=4,4'-bipyridine and bpe=1,2-bi(4-pyridyl)ethylene, have been prepared under hydrothermal condition. Complex 1 displays a 10 rigid linear chain structure while complex 2 displays 1D flexible zig-zag chain structure. Coordination number of the central Zn ion in complex 1 is six and in complex 2 is four. The structural differences of these complexes suggest the effect of size of the bridging ligands on the construction of metal organic frameworks with the same metal ion under solvothermal conditions. (C) 2013 Elsevier B.V. All rights reserved.